Вплив психологічного чинника людини на безпеку системи "Водій – Автомобіль – Дорога – Середовище" - Степанов, О. В. (НТУ "ХПІ", 2015)
У статті розглядається вплив психологічного чинника людини на безпеку комплексної системи "Водій – Автомобіль – Дорога – Середовище" (ВАДС). Доведено, що водій – це ланка комплексної системи ВАДС, функціями якого є прийняття рішення на основі опрацювання сприйнятої інформації і реалізація керуючих впливів. Визначено, що проблема безпеки дорожнього руху для свого вирішення потребує знань зв'язку між психофізіологічними показниками роботи водія та дорожніми умовами. Але оскільки такі відомості можуть бути здобуті лише емпірично, від дослідників, що вивчають питання надійності в плані підвищення безпеки дорожнього руху, потрібне проведення широких експериментальних робіт, що охоплюють практично всі аспекти діяльності водія. Автор доходить висновку, що надійність водія найбільшою мірою залежить від змісту і взаємозв'язку його психофізіологічних особливостей, підготовленості, працездатності, моральних якостей, стану здоров'я.

This article considers the impact of psychological human factor on safety of the complex Driver-Automobile-Road-Environment (DARE) system. The driver is proven to be a member of the complex DARE system, whose functions are decision-making on the basis of processing the information perceived, and performing the control actions. It is determined that the traffic safety issue to be solved it needs knowledge of relation between psychical and physiological parameters of driver’s operation and road conditions. The author points out that while such information may be obtained only empirically, the researchers who study the issues of reliability in plane of improving the road traffic safety are to carry out a wide range of experimental tasks which would cover almost all the aspects of driver’s activities in regard to psychical and physiological selection. In this case, in order to talk about usage of psychical and physiological selection, it is necessary to determine the criterion - a resultant characteristic, which may be evaluative. Unfortunately, the difference in definition of the criterion leads to obviously ambiguous and sometimes erroneous recommendations. The article describes the views on the necessity of keeping high reliability of driver. It attaches a special urgency to searching for modern methods for assessment drivers’ individual peculiarities. The article proves the idea that experience in experimental testing of the methods used for psychical and physiological selection of drivers shows that the methods which set high requirements for speed parameters of psychical activities that ensure drivers’ reliability are the most predicting ones. The author concludes that there acts a combination of psychological factors in field of road traffic safety. The factors which are directly related to the road traffic safety system are mostly determined by condition of the legal system, social discipline, legal conscience and legal culture of the population. At the same time reliability of the driver mainly depends on the matter and interrelation between his psychophysiology characteristics, preparedness, efficiency, moral characteristics and state of health.
Impact of psychological human factor on safety of the Driver – Automobile – Road – Environment system
Keywords: психологічний чинник; безпека; надійність водія; psychological factor; safety; reliability of the driver